RED ONION FARMERS COMMUNICATION NETWORK THROUGH PLANTING OF REFUGIA PLANT AS THE ADOPTION OF INTEGRATED PEST CONTROL (IPM) BASED ON ECOLOGICAL ENGINEERING IN NGANJUK REGENCY - Wuwun Risvita; Aulia Nadhirah; Septian Maulana Purnama (JURNAL AGRIMENT, 2022)
Nganjuk Regency is one of the highest red onion producers in East Java, but its productivity is not followed by a commensurate productivity yet. One of the causes is the attack of plant-disturbing organisms and chemical pesticides which are often the most effective way. Adoption of technological innovations for planting Refugia plants is an alternative in overcoming problems. Several roles of actors are needed to communicate with each other regarding this matter. This study aims to: 1) Analyze the communication network of farmers adopting technological innovations; (2) Analyzing the effect of farmers' characteristics and farming on the communication network; (3) Analyzing the effect of farmer communication networks on the adoption of technological innovations. The method used is a sociogram to determine the distribution of information on farmer groups and related parties. To determine the effect of the characteristics of farmers and farming on communication networks and the effect of communication networks on the adoption of technological innovations using regression analysis. The results of the study show that there is a role in the communication network, namely the head of each farmer group as opinion leader, active and dominant farmers as bridges and farmers who have other main jobs as isolated. Characteristics of farmers and farming have a significant effect on the communication network, so that it has a positive impact on the dissemination of information. The communication network also has a significant effect on the adoption of technological innovations so that the process of using the adoption of refugia plant innovations on red onion plants can be carried out because of the openness of farmers to existing information